2021
DOI: 10.21037/tp-21-314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cefuroxime axetil combined with Xingpi Yanger granules on the serum gastrin, motilin, and somatostatin levels in children with upper respiratory tract infection accompanied by diarrhea: results of a randomized trial

Abstract: Background: The purpose of the study was to investigate the effects of cefuroxime axetil combined with Xingpi Yanger granules on the treatment of upper respiratory tract infection accompanied by diarrhea and on serum gastrin (GAS), motilin (MOT), and somatostatin (SS) levels in children. Methods:In total, 124 children with upper respiratory tract infection accompanied by diarrhea admitted to the department of pediatrics in our hospital from May 2019 to May 2020 were selected and divided into a study group (n=6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…GAS is a potent hormone that promotes gastric acid secretion. The increase in GAS level may be related to sympathetic nerve excitation caused by trauma, continuous contraction of gastric mucosal blood vessels, vagus nerve choline fiber excitation caused by increased intracranial pressure, use of a strong dose of dehydrating agent and catabolic disorder[ 16 ]. Studies have found that when the level of serum GAS in critically ill patients increases, it will increase gastric acid secretion, resulting in transient small intestinal dysfunction and decreased gastric emptying capacity and gastric pyloric sphincter tension.…”
Section: Discussionmentioning
confidence: 99%
“…GAS is a potent hormone that promotes gastric acid secretion. The increase in GAS level may be related to sympathetic nerve excitation caused by trauma, continuous contraction of gastric mucosal blood vessels, vagus nerve choline fiber excitation caused by increased intracranial pressure, use of a strong dose of dehydrating agent and catabolic disorder[ 16 ]. Studies have found that when the level of serum GAS in critically ill patients increases, it will increase gastric acid secretion, resulting in transient small intestinal dysfunction and decreased gastric emptying capacity and gastric pyloric sphincter tension.…”
Section: Discussionmentioning
confidence: 99%
“…The brain-gut axis is the connecting channel between the gastrointestinal neuroendocrine and the central nervous system, which is closely related to the pathogenesis of functional diarrhea (23). GAS, MLT, and CCK are also in close relation to gastrointestinal function, among which GAS can improve the blood flow of gastric mucosa and enhance gastrointestinal motility (24). MLT can induce the release of pepsin and accelerate gastrointestinal motility and emptying (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…In eight of the nine studies, herbal medicines were used alone, and in the remaining study (Ren et al, 2021), herbal medicines and an antibiotic (cefuroxime) were used in combination. Seven studies were conducted on patients with GI diseases or symptoms, one included patients with psychiatric symptoms, and the remaining included healthy individuals.…”
Section: Description Of the Rct Studiesmentioning
confidence: 99%
“…Herbal formulas have been used as alternatives to Western medicine for treating GI symptoms such as constipation, diarrhea, and dyspepsia (Zhang et al, 2013;Zhang and Guo, 2015;Ren et al, 2021). Furthermore, several herbal medicines have been reported to affect plasma MLN levels.…”
Section: Introductionmentioning
confidence: 99%